Predicting historical oxygen deficiency areas in the western Baltic Sea: A multi-model approach - Sarah Piehl; Jacob Carstensen; Thomas Neumann; Clarissa Vock (Marine Pollution Bulletin, 2025)

Can Solar‐Powered Irrigation Systems Naturally Meet Crop Water Requirements? Proof of Concept From a Case Study in Sub‐Saharan Africa - Eric Oppong Danso; Christiana Dietzen; William Akortey; Bernard Kwabena Boadi Mensah; Peter Bilson Obour; John Bright Amoah Nyasapoh; Ebenezer Agyapong; Elorm Grace Ayayi; Nana Oduro Osei Bonsu; Michael Osei Adu; Emmanuel Arthur; Jacob Ulzen; et al. (Irrigation and Drainage, 2025)
Irrigation scheduling is crucial for ensuring precise water delivery to crops. However, in many sub‐Saharan African irrigation schemes, water is applied without considering crop water needs, resulting in low crop water productivity and low yields. Solar‐powered irrigation systems can automatically meet these needs by utilizing solar radiation, which drives both evapotranspiration and solar panel power production for pumping. This study aimed to integrate irrigation scheduling into a solar‐driven irrigation system and assess the impact of meteorological variables on reference evapotranspiration (ET o ) in Ghana. A 50‐watt solar panel powered a 12‐V submersible pump, with a flow meter installed on the outlet pipe for hourly volume of water pumped (VWP) data readings. These data were used to examine correlations between solar radiation (R s ) and ET o , as well as between R s and VWP. Partial correlation analyses were used to assess the relative influences of R s , wind speed (U 2 ), relative humidity (RH) and air temperature (T air ) on ET o across 10 locations in Ghana's agroecological zones. The study revealed a strong linear correlation between the hourly R s and ET o ( R 2 > 0.9) and between the hourly R s and VWP ( R 2 = 0.8). The VWP was sufficient to meet crop‐water demand year‐round. Solar radiation was consistently the primary meteorological factor influencing ET o in Ghana.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

TGFβ signalling pathway impacts brain metastases profiles in locally advanced colorectal cancer - Sven Jacob; Ilja Balonov; Vindi Jurinovic; Christian Heiliger; Tengis Tschaidse; Jörg Kumbrink; Thomas Kirchner; Jens Werner; Martin K. Angele; Marlies Michl; Jens Neumann (Clinical & Experimental Metastasis, 2024)
Rationale Colorectal Cancer (CRC) represents the third most common type of cancer in Germany and the second most common cancer-related cause of death worldwide. Distant metastases are still the main limit for patient survival. While liver metastases as well as peritoneal carcinomatosis can often either be resected or treated with systemic therapy, little options remain for brain metastases. Additionally, a number of studies has already investigated hepatic, peritoneal, pulmonary as well as continuing distant metastases in colorectal cancer. Yet, with respect to tumor biology and brain metastases, little is known so far. Material and methods Two cohorts, M0 without distant spread and BRA with brain metastases were build. RNA was isolated from paraffin embedded specimen. Gene expression was performed by an RNA NanoString-Analysis using the nCounter® PanCancer Progression Panel by NanoString-Technologies (Hamburg, Germany). Results were analysed by principal component analysis, gene expression and pathway analysis using commonly available databases such as KEGG as benchmark for comparison. Results We were able to determine a gene signature that provides a sophisticated group separation between M0 and BRA using principal component analysis. All genes with strong loading characteristics on principal component 1 were cross-referenced with the subsequently performed accurate gene set enrichment analysis (GSEA). The GSEA revealed a clear dysregulation of the TGFβ pathway in compared cohorts M0 and BRA. Interestingly, the targeted pathways analysis of the identified genes confirmed that in fact almost all strong loading genes of PC1 play a role in the TGFβ pathway. Conclusion Our results suggest the TGFβ pathway as a crucial player in the development of brain metastases in primary CRC. In some types of colorectal cancer, downregulation of the TGFβ pathway might hinder primary colorectal cancer to metastasize to the nervous system. While the paradoxical functioning of the TGFβ pathway is still not fully understood, these shed light on yet another clinical implication of this complex pathway.

Initial characterization of a transgenic mouse with overexpression of the human D1-dopamine receptor in the heart - Lina Maria Rayo Abella; Hannes Jacob; Christin Hesse; Britt Hofmann; Sarah Schneider; Lisa Schindler; Max Keller; Igor B. Buchwalow; CongYu Jin; Pertti Panula; Stefan Dhein; Jan Klimas; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Dopamine can exert effects in the mammalian heart via five different dopamine receptors. There is controversy whether dopamine receptors increase contractility in the human heart. Therefore, we have generated mice that overexpress the human D 1 -dopamine receptor in the heart (D 1 -TG) and hypothesized that dopamine increases force of contraction and beating rate compared to wild-type mice (WT). In D 1 -TG hearts, we ascertained the presence of D 1 -dopamine receptors by autoradiography using [ 3 H]SKF 38393. The mRNA for human D 1 -dopamine receptors was present in D 1 -TG hearts and absent in WT. We detected by in-situ-hybridization mRNA for D 1 -dopamine receptors in atrial and ventricular D 1 -TG cardiomyocytes compared to WT but also in human atrial preparations. We noted that in the presence of 10 µM propranolol (to antagonize β-adrenoceptors), dopamine alone and the D 1 - and D 5 -dopamine receptor agonist SKF 38393 (0.1–10 µM cumulatively applied) exerted concentration- and time-dependent positive inotropic effects and positive chronotropic effects in left or right atrial preparations from D 1 -TG. The positive inotropic effects of SKF 38393 in left atrial preparations from D 1 -TG led to an increased rate of relaxation and accompanied by and probably caused by an augmented phosphorylation state of the inhibitory subunit of troponin. In the presence of 0.4 µM propranolol, 1 µM dopamine could increase left ventricular force of contraction in isolated perfused hearts from D 1 -TG. In this model, we have demonstrated a positive inotropic and chronotropic effect of dopamine. Thus, in principle, the human D 1 -dopamine receptor can couple to contractility in the mammalian heart.

Lysergic acid diethylamide stimulates cardiac human H2 histamine and cardiac human 5-HT4-serotonin receptors - Ulrich Gergs; Hannes Jacob; Pauline Braekow; Britt Hofmann; Steffen Pockes; Laura J. Humphrys; Uwe Kirchhefer; Charlotte Fehse; Joachim Neumann (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Lysergic acid diethylamide (LSD) is an artificial hallucinogenic drug. Thus, we hypothesized that LSD might act 5-HT 4 serotonin receptors and/or H 2 histamine receptors. We studied isolated electrically stimulated left atrial preparations, spontaneously beating right atrial preparations, and spontaneously beating Langendorff-perfused hearts from transgenic mice with cardiomyocyte-specific overexpression of the human 5-HT 4 receptor (5-HT 4 -TG) or of the H 2 -histamine receptor (H 2 -TG). For comparison, we used wild type littermate mice (WT). Finally, we measured isometric force of contraction in isolated electrically stimulated muscle strips from the human right atrium obtained from patients during bypass surgery. LSD (up to 10 µM) concentration dependently increased force of contraction and beating rate in left or right atrial preparations from 5-HT 4 -TG ( n = 6, p < 0.05) in 5-HT 4 -TG atrial preparations. The inotropic and chronotropic effects of LSD were antagonized by 10 µM tropisetron in 5-HT 4 -TG. In contrast, LSD (10 µM) increased force of contraction and beating rate in left or right atrial preparations, from H 2 -TG. After pre-stimulation with cilostamide (1 µM), LSD (10 µM) increased force of contraction in human atrial preparations ( n = 6, p < 0.05). The contractile effects of LSD in human atrial preparations could be antagonized by 10 µM cimetidine and 1 µM GR 125487. LSD leads to H 2 -histamine receptor and 5-HT 4 -receptor mediated cardiac effects in humans.

Ergometrine stimulates histamine H2 receptors in the isolated human atrium - Hannes Jacob; Pauline Braekow; Britt Hofmann; Uwe Kirchhefer; Lisa Forster; Denise Mönnich; Laura J. Humphrys; Steffen Pockes; Joachim Neumann; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Ergometrine (6a R ,9 R )- N -(( S )-1-hydroxypropan-2-yl)-7-methyl-4,6,6a,7,8,9-hexa-hydro-indolo-[4,3- fg ]chinolin-9-carboxamide or lysergide acid β-ethanolamide or ergonovine) activates several types of serotonin and histamine receptors in the animal heart. We thus examined whether ergometrine can activate human serotonin 5-HT 4 receptors (h5-HT 4 R) and/or human histamine H 2 receptors (hH 2 R) in the heart of transgenic mice and/or in the human isolated atrium. Force of contraction or beating rates were studied in electrically stimulated left atrial or spontaneously beating right atrial preparations or spontaneously beating isolated retrogradely perfused hearts (Langendorff setup) of mice with cardiac specific overexpression of the h5-HT 4 R (5-HT 4 -TG) or of mice with cardiac specific overexpression of the hH 2 R (H 2 -TG) or in electrically stimulated human right atrial preparations obtained during cardiac surgery. Western blots to assess phospholamban (PLB) phosphorylation on serine 16 were performed. Ergometrine exerted concentration- and time-dependent positive inotropic effects and positive chronotropic effects in atrial preparations starting at 0.3 µM and reaching a plateau at 10 µM in H 2 -TGs ( n = 7). This was accompanied by an increase in PLB phosphorylation at serine 16. Ergometrine up 10 µM failed to increase force of contraction in left atrial preparations from 5-HT 4 -TGs ( n = 5). Ten micrometer ergometrine increased the force of contraction in isolated retrogradely perfused spontaneously beating heart preparations (Langendorff setup) from H 2 -TG but not 5-HT 4 -TG. In the presence of the phosphodiesterase inhibitor cilostamide (1 µM), ergometrine at 10 µM exerted positive inotropic effects in isolated electrically stimulated human right atrial preparations, obtained during cardiac surgery, and these effects were eliminated by 10 µM of the H 2 R antagonist cimetidine but not by 10 µM of the 5-HT 4 R antagonist tropisetron. Furthermore, ergometrine showed binding to human histamine H 2 receptors (at 100 µM and 1 mM) using HEK cells in a recombinant expression system (p K i < 4.5, n = 3). In conclusion, we suggest that ergometrine is an agonist at cardiac human H 2 Rs.

Near equatorial paleoclimatic evolution and control on organic matter accumulation during the Cenomanian in the Abu Gharadig Basin, southern Tethys: Insights from palynology, organic petrography, and geochemistry - Ahmed Mansour; Thomas Gentzis; Sameh S. Tahoun; Mohamed S. Ahmed; Susanne Gier; Humberto Carvajal-Ortiz; Jacob Neumann; Xiugen Fu; Jian Wang (International Journal of Coal Geology, 2023)

Paleoenvironmental, paleoclimatic, and organic matter assessment of the hybrid Kharita Formation (Albian) in the Abu Gharadig Basin, Egypt: Integration between palynology, organic petrography, and organic geochemistry - Ahmed Mansour; Thomas Gentzis; Sameh S. Tahoun; Mohamed S. Ahmed; Michael Wagreich; Humberto Carvajal-Ortiz; Jacob Neumann; Ahmed E. Radwan (Marine and Petroleum Geology, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Climate effects on US infrastructure: the economics of adaptation for rail, roads, and coastal development - James E. Neumann; Paul Chinowsky; Jacob Helman; Margaret Black; Charles Fant; Kenneth Strzepek; Jeremy Martinich (Climatic Change, 2021)
Changes in temperature, precipitation, sea level, and coastal storms will likely increase the vulnerability of infrastructure across the USA. Using models that analyze vulnerability, impacts, and adaptation, this paper estimates impacts to railroad, roads, and coastal properties under three infrastructure management response scenarios: No Adaptation; Reactive Adaptation, and Proactive Adaptation. Comparing damages under each of these potential responses provides strong support for facilitating effective adaptation in these three sectors. Under a high greenhouse gas emissions scenario and without adaptation, overall costs are projected to range in the $100s of billions annually by the end of this century. The first (reactive) tier of adaptation action, however, reduces costs by a factor of 10, and the second (proactive) tier reduces total costs across all three sectors to the low $10s of billions annually. For the rail and road sectors, estimated costs for Reactive and Proactive Adaptation scenarios capture a broader share of potential impacts, including selected indirect costs to rail and road users, and so are consistently about a factor of 2 higher than prior estimates. The results highlight the importance of considering climate risks in infrastructure planning and management.